Tanggung Jawab Hukum Penerbitan Sertifikat Hak Milik Di Wilayah Laut Indonesia Dalam Persfektif Siyasah Idariyah - Alfi Rahma Dhani; Husni Bin Abdul Jalil; T Surya Reza (Journal of Innovative and Creativity, 2025)
This study discusses the issuance of Land Ownership Certificates (SHM) in Indonesian maritime areas that are contrary to the provisions of agrarian law and land administration. Based on Articles 4 and 5 of Law Number 5 of 1960 concerning Agrarian Principles (UUPA), and Article 9 of Government Regulation Number 24 of 1997 concerning Land Registration, maritime areas are not included in land objects that can be privately owned because they are public property controlled by the state. However, there are practices of issuing SHM in the PIK 2 maritime area that should not be able to be certified. This study uses a normative juridical method with a statute approach and a case approach. Data collection techniques are carried out through literature studies and analyzed qualitatively. The results of the study indicate that there is legal responsibility by three main parties. First, the village head is responsible for issuing land certificates (SKT) without verifying the boundaries and status of the land, including in maritime areas that are not under his authority. Second, Land Deed Officials (PPAT) are responsible if they continue to issue deeds for land located in maritime or state territory that do not meet legal requirements, thereby violating the principle of legality. Third, the National Land Agency (BPN) is responsible for continuing to issue certificates over maritime territory, even though the area is legally ineligible for certification. These three parties can be subject to administrative, civil, and even criminal sanctions depending on the violations. From an Islamic perspective, through the concept of siyasah idariyah, these actions also contradict the principles of justice, trustworthiness, and public welfare. Therefore, strict supervision and administrative corrections are needed to ensure that land policies align with national law and Islamic sharia values